Promoting resilience among family caregiver of cancer through Islamic religious coping - Saputro, Iswan; Nashori, Fuad; Sulistyarini, Rr. Indahria (Universitas Muhammadiyah Surakarta, 2021)
The burden of the family caregivers in providing care to family members who have cancer can reduce resilience. This study aimed to evaluate the effectiveness of religious coping training to enhance the resilience in the sample of family caregivers of cancer disease. Eight family caregivers of cancer disease participated in this study. The participants were divided into intervention group (n = 4) and control group (n = 4). The pre-test post-test control group design was used in this study as the research design and assessed at three points (pre-intervention, post-intervention, and 2-week follow-up). The participants completed the Connor-Davidson Resilience Scale (CD-RISC) to assess any changes in resilience. An intervention module was prepared based upon Pargament, Smith, Koenig, and Perez (1998) and modified using Islamic coping strategies based upon the positive religious coping concept. The results showed that the intervention group participants reported a significant increase in resilience compared with the control group. Participants also reported positive changes in interpreting the role of family caregivers. This study discussed the implications and limitations of the finding.